2017
DOI: 10.1089/cyber.2016.0126
|View full text |Cite
|
Sign up to set email alerts
|

Social Big Data Analysis of Information Spread and Perceived Infection Risk During the 2015 Middle East Respiratory Syndrome Outbreak in South Korea

Abstract: We investigated online diffusion of information, spread of fear, and perceived risk of infection to Middle East Respiratory Syndrome (MERS) as cases of MERS spread rapidly and dozens of fatalities occurred in South Korea in May-June of 2015. This study retrieved 8,671,695 MERS-related online documents from May 20 to June 18, 2015, from 171 Korean online channels and analyzed such documents by using multilevel models and data mining with Apriori algorithm association analysis. We used R software (version 3.2.1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 7 publications
1
56
0
2
Order By: Relevance
“…In such a situation, an infectious disease outbreak can trigger the ordinary public's expression of their concerns about the outbreak, particularly through social media (Ofoghi, Mann, & Verspoor, 2016). For example, self-relevant emotions such as fear and anger were prevalent when people talked about the 2015 MERS outbreak on social media (Song, Song, Seo, Jin, & Kim, 2017). A recent study revealed that fear and anger were consistently expressed in tweets during the Ebola outbreak (Ofoghi et al, 2016).…”
Section: The Effects Of Social Media Exposure On Self-relevant Emotionsmentioning
confidence: 99%
“…In such a situation, an infectious disease outbreak can trigger the ordinary public's expression of their concerns about the outbreak, particularly through social media (Ofoghi, Mann, & Verspoor, 2016). For example, self-relevant emotions such as fear and anger were prevalent when people talked about the 2015 MERS outbreak on social media (Song, Song, Seo, Jin, & Kim, 2017). A recent study revealed that fear and anger were consistently expressed in tweets during the Ebola outbreak (Ofoghi et al, 2016).…”
Section: The Effects Of Social Media Exposure On Self-relevant Emotionsmentioning
confidence: 99%
“…Concerning another coronavirus, Song and coworkers [18] investigated online diffusion of information, spread of fear, and perceived risk of contracting MERS infection during the MERS outbreak in South Korea in May-June of 2015. Buzz conveying negative feelings was found to be more prevalent in online discussion boards, Twitter, and online cafes than news sites and blogs.…”
Section: Short-term Applications Of Artificial Intelligence and Big Dmentioning
confidence: 99%
“…Recent studies have used big data analytics to demonstrate that people mentioned and/or shared factual information related to MERS, such as symptoms and prevention methods, in online media platforms, including social media (Song, 2015). Moreover, negative emotions concerning the disease, such as anxiety or fear, were more prevalent than positive emotions in social media during the infectious outbreak (Song, Song, Seo, Jin, & Kim, 2017).…”
Section: Social Media and Risk Perceptionmentioning
confidence: 99%